Lignin and Functional Polymer-Based Materials: Synthesis, Characterization and Application for Cr (Vi) and as (V) Removal from Aqueous Media - Negrete-Vergara, C; Negrete-Vergara, C; Salfate-Calderon, G (Elsevier B.V., 2024)
In this study, lignin derived from corncobs was chemically modified by substituting the hydroxyl groups present in its structure with methacrylate groups through a catalytic reaction using methacrylic anhydride, resulting in methacrylated lignin (ML). These MLs were incorporated in polymerization reaction of the monomer 2-[(acryloyloxy)ethyl trimethylammonium] chloride (Cl-AETA) and Cl-AETA, Cl-AETA/ML polymers were obtained, characterized (spectroscopic, thermal and microscopic analysis), and evaluated for removing Cr (VI) and As (V) from aqueous media in function of pH, contact time, initial metal concentrations and adsorbent amount. The Cl-AETA/ML polymers followed the Langmuir adsorption model for the evaluated metal anions and were able to remove up to 91 % of Cr (VI) with a qmax (maximum adsorption capacity) of 201 mg/g, while for As (V), up to 60 % could be removed with a qmax of 58 mg/g. The results demonstrate that simple modifications in lignin enhance its functionalization and properties, making it suitable for removing contaminants from aqueous media, showing promising results for potential future applications. © 2024 Elsevier B.V.